2008
DOI: 10.1287/mksc.1070.0282
|View full text |Cite
|
Sign up to set email alerts
|

The Retail Value Chain: Linking Employee Perceptions to Employee Performance, Customer Evaluations, and Store Performance

Abstract: The authors test a value chain model entailing a progression of influence from retail employee job perceptions -> retail employee job performances -> customer evaluations -> customer spending and comparable store sales growth. The authors test the model using three matched samples of 1,615 retail employees, 57,656 customers, and 306 stores of a single retail chain. The authors find that three retail employee job perceptions (conscientiousness, perceived organizational justice, and organizational identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 43 publications
1
92
0
8
Order By: Relevance
“…The link between employee satisfaction and a variety of outcomes (such as customer satisfaction, productivity, and profit) has also been established by Harter et al (2002). In a retail setting, Maxham et al (2007) found that employee performance and perceptions influence customer evaluations of the retailer, which, in turn, affects store performance. Kamakura et.al (2002) provided general support for the service chain but note that firms must be careful to effectively manage both the employee inputs as well as customer perceptions in order to increase profitability.…”
Section: The Satisfaction-based Path Of the Service Profit Chainmentioning
confidence: 95%
“…The link between employee satisfaction and a variety of outcomes (such as customer satisfaction, productivity, and profit) has also been established by Harter et al (2002). In a retail setting, Maxham et al (2007) found that employee performance and perceptions influence customer evaluations of the retailer, which, in turn, affects store performance. Kamakura et.al (2002) provided general support for the service chain but note that firms must be careful to effectively manage both the employee inputs as well as customer perceptions in order to increase profitability.…”
Section: The Satisfaction-based Path Of the Service Profit Chainmentioning
confidence: 95%
“…Empirical evidence also points to the importance of treating employees with respect and dignity (Ramaswami and Singh 2003), compensating them fairly (Maxham et al 2008;Ramaswami and Singh 2003), and recognizing them for their efforts (Kohli 1985). For instance, a study of merit pay fairness for industrial salespeople found that interactional fairness, which focuses on the social enactment of procedures, is an important determinant of job satisfaction (Ramaswami and Singh 2003).…”
Section: Employeesmentioning
confidence: 99%
“…A number of variables feature prominently: perceived service quality, perceived value, customer satisfaction, and behavioural intentions (Cronin et al, 2000;Maxham et al, 2008). Service quality is how well a delivered service matches customers' expectations of that service (Parasuraman et al, 1988).…”
Section: Retail Service Evaluationmentioning
confidence: 99%